Navigating Religious Difference in Spiritual Care and Counseling Essays in Honor of Kathleen J. Greider - Snodgrass, Jill L. (Claremont Studies in Interreligious Dialogue, 2019)
This volume explores themes, models and issues related to pastoral care and counseling in diverse religious contexts, including theistic and nontheistic traditions.